Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\textsf{Barra inteira}\rightarrow\mathsf{\dfrac{6}{6}}[/tex]
[tex]\textsf{Ant{\^o}nio}\rightarrow\mathsf{\dfrac{1}{2}}[/tex]
[tex]\textsf{Bernardo}\rightarrow\mathsf{\dfrac{1}{3}}[/tex]
[tex]\textsf{Carlos}\rightarrow\mathsf{\dfrac{6}{6} - \dfrac{1}{2} - \dfrac{1}{3} = \dfrac{6 - 3 - 2}{6} = \dfrac{1}{6}}[/tex]
[tex]\boxed{\boxed{\boxed{\textsf{Carlos}\rightarrow\mathsf{\dfrac{1}{6}}}}}[/tex]
Olá!!!
Resposta...
_____________________
Sabemos que:
[tex]\boxed{ \begin{array}{lr} \tt Barra \ inteira = \dfrac{6}{6} \\ \\ \tt Ant\´{o}nio = \dfrac{1}{2} \\ \\ \tt Bernardo = \dfrac{1}{3} \\ \\ \tt Carlos = x \end{array}}[/tex]
Então, fazemos a subtração:
[tex]\boxed{ \begin{array}{lr} \tt \bf Logo \ abaixo:\\ \\ \tt = \dfrac{6}{6}-\dfrac{1}{2}-\dfrac{1}{3} \\ \\ \tt =\dfrac{6-3-2}{6} \\ \\ \tt \bf =\dfrac{1}{6} \end{array}}[/tex]
![Ver imagem PRAZERMRXOFICIAL](https://pt-static.z-dn.net/files/dd5/9d7de587e3aea590cac003d65f331a0a.jpg)